2017
DOI: 10.1177/1687814017744122
|View full text |Cite
|
Sign up to set email alerts
|

Cross modal strain energy–based structural damage detection in the presence of noise effects

Abstract: When conducting damage assessment by cross modal strain energy method, two very different approaches can be employed to solve cross modal strain energy equations. However, there are no performance comparison between these two approaches on their efficiency and effectiveness, especially under noise-polluted situations. In this article, cross modal strain energy method together with these two solving approaches, locality and wholeness approaches, is summarized, and their intrinsic features are extensively discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…This operation can overcome the problem of the incomplete modal parameters under natural load excitation. Xu and Wang [30] summarized the cross-modal strain energy method and developed a two-stage methodology for damage assessment. The wholeness strain energy approach is first utilized for roughly localizing the potentially damaged members, and then the final damage locations and associated extents are exactly estimated with the locality strain energy approach.…”
Section: Introductionmentioning
confidence: 99%
“…This operation can overcome the problem of the incomplete modal parameters under natural load excitation. Xu and Wang [30] summarized the cross-modal strain energy method and developed a two-stage methodology for damage assessment. The wholeness strain energy approach is first utilized for roughly localizing the potentially damaged members, and then the final damage locations and associated extents are exactly estimated with the locality strain energy approach.…”
Section: Introductionmentioning
confidence: 99%
“…As a special case of modal curvature methods, modal strain energy methods have come forth in damage detection literature (Baneen and Kausar, 2018). It was shown that the modal strain energy methods are well capable of finding damage location (Cha and Buyukozturk, 2015; Xu and Wang, 2017; Yan et al, 2012). Commonly, damage/crack identification problems have been considered as the inverse problem of mechanics.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Li et al and Wang et al both extended the cross‐modal strain energy (CMSE) method to localize the damage and estimate its severity concurrently. Subsequently, many overdetermined systems of linear equations have been solved based on different hypotheses using the CMSE method . Likewise, Shi et al identified structural damage by constructing an overdetermined system related to the sensitivity coefficient of the modal strain energy change ratio (MSECR) to the damage.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, many overdetermined systems of linear equations have been solved based on different hypotheses using the CMSE method. 5 Likewise, Shi et al 6 identified structural damage by constructing an overdetermined system related to the sensitivity coefficient of the modal strain energy change ratio (MSECR) to the damage. However, the coefficient matrix of an overdetermined system is typically ill conditioned due to the presence of modeling errors, measurement noise, and modal incompleteness; as a result, an erroneous solution that is not in accordance with the actual situation but still seems to effectively satisfy the system can usually be obtained.…”
Section: Introductionmentioning
confidence: 99%